The Impact of CEO Characteristics on Organizational Culture and on the Silo Effect - Mouta, Cristina; Meneses, Raquel (Review of Business Management, 2021)
Purpose – The purpose of the study is to understand the impact of psychological and observable CEO characteristics on organizational culture and silos. Design/methodology/approach – A questionnaire was built using information collected during the literature review stage and emailed to the firm decision-makers. Using survey data from 185 small-to-medium-sized firms from two sectors – accommodation and food, beverage, and tobacco – a structural equation model was applied to determine if the theoretical model could be confirmed or not, and the partial least squares technique was used to check if certain relationships exist. Findings – General support was found for a theoretical model in which CEO personality traits, particularly conscientiousness, openness to experience, and extraversion, influence both organizational culture and silos, and observable variables such as age and management tenure influence the ability of the firm to develop internal coordination competences, thus inhibiting the appearance of silos. Originality/value – The main contribution to the knowledge lies in the combination of different theoretical frameworks and the empirical approach used to test the importance of CEO characteristics in organizations and in their ability to develop cooperation networks. Keywords – CEO, Big Five Framework, Competing Values Framework, Organizational Culture, Silos.